Analysis of Student Interest in Tahfidz Qur'an Extracurricular at Elementary School: Analisis Minat Siswa Terhadap Ekstrakurikuler Tahfidz Qur'an di SD - Hanifatul Mukarromah; Anita Pujiastutik (Academia Open, 2022)
This article aims to find out about the implementation and interest of students in extracurricular tahfidz Qur'an at SD Muhammadiyah 1 Krembung. This study uses a qualitative method, an interactive approach. The subjects of this study were the Deputy Head of Curriculum, extracurricular tahfidz Qu r'an teachers and students who took tahfidz Qur'an extracurricular activities. The results showed that the implementation of extracurricular tahfidz Qur'an runs 1 meeting a week. Many students of SD Muhammadiyah 1 Krembung are interested in extracurricular tahfidz Qur'an. This can be shown by the participation of students in each class in extracurricular tahfidz Qur'an.